Avaliação do conhecimento sobre aleitamento materno de puérperas atendidas em um hospital universitário - Rabelo, Alderi Lopes (2013)
Breastfeeding plays an important role in reducing neonatal and infant mortality. Women s knowledge and attitudes have an impact on several aspects of breastfeeding, such as its establishment and duration. The present study aimed to evaluate the knowledge and factors interfering the establishment of breastfeeding among postpartum women of the Hospital of the Federal University of Uberlandia (Hospital das Clínicas da Universidade Federal de Uberlandia [HC-UFU]). This is a quantitative study of cross-sectional conducted at Hospital of the Federal University of Uberlandia. The study included all women staying in rooming from July 1 to December 31, 2010 who agreed to participate and had no contraindication to breastfeed. An interview was used to obtain data on breastfeeding. We assessed sociodemographic variables, obstetric profile and information on breastfeeding from interviewed women. During the study period, 958 women remained in rooming during hospitalization and 907 were interviewed. The study revealed that the majority of the puerperal women were young, with stable union, good schooling, realized prenatal in public service, decided to breastfeed before pregnancy and intend to breastfeed their infants for 12 months. Prenatal was mentioned as the main source of information about breastfeeding and nursing professionals were indicated as the main professional category responsible for guidance and assistance on establishment of breastfeeding. The results obtained in this study suggest that the training of health professionals, particularly nursing staff, could change the practice of breastfeeding.